STUDI TENTANG ZIRKONIA (ZrO2) DAN APLIKASI ZIRKONIA TERSTABILKAN MAGNESIA (MgPSZ) SEBAGAI MATERIAL DENTAL BLOCK - Dedek Yusuf Pulungan (Jambura Journal of Chemistry, 2021)
Zirconia (ZrO2) is a zirconium metal oxide which has superior toughness, strength, good resistance and biocompatibility. ZrO2 has three polymorphic phases: monoclinic (m-ZrO2), tetragonal (t-ZrO2) and cubic (c-ZrO2). Various types of zirconia ceramics for dental material applications such as tetragonal zirconia doped with yttrium cations (Y-TZP), zirconia doped with magnesium cations (Mg-PSZ) and zirconia reinforced alumina (ZTA). In general, zirconia is doped with a stabilizer to maintain its structure at room temperature. A stabilizer that has been developed using magnesia (MgO). Magnesia-stabilized zirconia is generally called Mg-PSZ. The process of molding dental block materials usually utilizes Computer Aided Design and Computer Aided Manufacturing (CAD / CAM) technology and the glasing process. Dental block material self-tests are currently being performed in vivo on mice. Studies on dental block materials, especially Mg-PSZ, are very important so that the use of Mg-PSZ in the field of dental restoration can develop rapidly in the future.